2007
DOI: 10.1002/ejic.200700727
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic and Structural Systematics of Complexes of Germanium(IV) Halides (GeX4, X = F, Cl, Br or I) with Mono‐, Bi‐ and Tri‐Dentate and Macrocyclic Nitrogen Donor Ligands

Abstract: The six‐coordinate adducts cis‐[GeX4(L–L)] (L–L = 2,2′‐bipyridyl, 1,10‐phenanthroline, or Me2NCH2CH2NMe2, X = F, Cl or Br) have been synthesised and characterised by IR and VT 1H and 19F{1H} NMR spectroscopy. X‐ray crystal structures reveal distorted octahedral geometries and the trends in d(Ge–N) with halide are interpreted in terms of varying Lewis acidity within the series. The trans‐[GeX4(py)2] were similarly characterised. In contrast, GeI4 does not form similar adducts, although it appears to co‐crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 26 publications
2
45
0
1
Order By: Relevance
“…6,96 Many Ge(IV) complexes are moisture sensitive, whilst the thermal stability of Ge(II) complexes is often poor. Among the Ge(II) complexes explored were the commercially available GeBr 2 , a complex of the functionalised diimine [GeCl 2 (4,4 0 -didecyl-2,2 0bipyridyl)], 6 97 These two reagents were chosen as they are thermally relatively stable, and since they are coordinatively saturated, they are moisture stable solids and relatively resistant to hydrolysis in solution. Unfortunately, they proved to be insufficiently soluble in the SCFs.…”
Section: Reagentsmentioning
confidence: 99%
“…6,96 Many Ge(IV) complexes are moisture sensitive, whilst the thermal stability of Ge(II) complexes is often poor. Among the Ge(II) complexes explored were the commercially available GeBr 2 , a complex of the functionalised diimine [GeCl 2 (4,4 0 -didecyl-2,2 0bipyridyl)], 6 97 These two reagents were chosen as they are thermally relatively stable, and since they are coordinatively saturated, they are moisture stable solids and relatively resistant to hydrolysis in solution. Unfortunately, they proved to be insufficiently soluble in the SCFs.…”
Section: Reagentsmentioning
confidence: 99%
“…Some time ago, solution-phase NMR studies [34] found that N-donor -TiF 4 and SnF 4 , complexes assumed cis geometries in spite of steric considerations, which would place the larger substituents opposite one another in a trans configuration. Interestingly, (CH 3 CN) 2 GeF 4 , is a convenient reagent for the preparation of various octahedral GeF 4 L 2 complexes [35,36], because it is reasonably stable and the CH 3 CN ligands are fairly labile, while pure GeF 4 is less convenient because it is gas at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The lengths of Ge-O bonds in it vary in the narrow range (1.847-1.863 A, Table 1), Scheme 1 Synthesis of 1-3. 26 In crystal structure of 3 (Fig. 2), aromatic C-H groups form weak C-H/O interactions with oxygen atoms of 2,3-dihydroxynaphthalene ligands.…”
Section: Resultsmentioning
confidence: 99%